2015
DOI: 10.1007/s00464-015-4211-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic suturing learning curve in an open versus closed box trainer

Abstract: BackgroundThe aim of this study was to examine the influence of training under direct vision prior to training with indirect vision on the learning curve of the laparoscopic suture task.MethodsNovices were randomized in two groups. Group 1 performed three suturing tasks in a transparent laparoscopic box trainer under direct vision followed by three suturing tasks in a standard non-transparent laparoscopic box trainer equipped with a 0° laparoscope. Group 2 performed six suturing tasks in a standard laparoscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…2 Accordingly, efficient teaching of the laparoscopic technique is paramount to achieving safe and widespread use of this technology. The beneficial effects of practical skills training in laparoscopic simulators such as black boxes or high-fidelity simulators to improve surgical performance have been investigated and discussed in several studies [3][4][5][6][7][8][9] and reviews. 10,11 Pearson et al showed that structured training significantly improves laparoscopic suturing skills, 5 which is the most difficult, rate-limiting step that requires time to master.…”
Section: Introductionmentioning
confidence: 99%
“…2 Accordingly, efficient teaching of the laparoscopic technique is paramount to achieving safe and widespread use of this technology. The beneficial effects of practical skills training in laparoscopic simulators such as black boxes or high-fidelity simulators to improve surgical performance have been investigated and discussed in several studies [3][4][5][6][7][8][9] and reviews. 10,11 Pearson et al showed that structured training significantly improves laparoscopic suturing skills, 5 which is the most difficult, rate-limiting step that requires time to master.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report indicated that the mirror visual feedback improved the motor performance of the hand in a neurophysiological study 25. Rodrigues et al 19. reported that novices benefit from starting their training with difficult basic laparoscopic skills in a transparent box trainer.…”
Section: Discussionmentioning
confidence: 98%
“…Various methods were introduced to objectively evaluate basic laparoscopic surgical skills, such as the virtual reality simulator system and physical trial program 17, 18, 19, 20. However, the influence of real‐time visual feedback for laparoscopic surgical training has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classicamente, a grande dificuldade na capacitação em procedimentos laparoscópicos é a aquisição da competência para trabalhar em duas dimensões com a visão direcionada para o monitor e a manipulação do instrumental sem visão direta, percepção de profundidade alterada, campo de trabalho reduzido, posição fixa dos trocartes, além da percepção de inversão dos movimentos das pinças (efeito fulcral) e perda da percepção háptica 4 devido à resistência dentro dos trocartes e aos instrumentos cirúrgicos longos 5 . Essas particularidades fazem que a capacitação na técnica laparoscópica apresente singularidades e abordagens próprias 6 .…”
unclassified